Vitamin D and curcumin-loaded PCL nanofibrous for engineering osteogenesis and immunomodulatory scaffold - Al-Bishari, Abdullrahman M.; Al-Shaaobi, Bilal A.; Al-Bishari, Aisha A.; Al-Baadani, Mohammed A.; Yu, Liang; Shen, Jiating; Cai, Lei; Shen, Yiding; Deng, Zhennan; Gao, Peng (Frontiers in Bioengineering and Biotechnology, 2022)
The accelerating bone healing process is still a major challenge in clinical orthopedics, especially in critical-sized bone defects. Recently, Nanofiber membranes are showing increasing attention in the biomedical field due to their good biocompatibility, mechanical stability, and the ability to work as a drug carrier to achieve localized and sustained drug delivery. Herein, a multifunction nanofiber membrane loaded with vitamin D (Vit D) and curcumin (Cur) was successfully fabricated using electrospinning technology. In addition, we innovatively modified Vit D with PEG to improve the hydrophilicity of PCL nanofibers. The vitro results of CCK-8, alkaline phosphatase (ALP) and mineralization demonstrated that the PCL/Vit D-Cur membrane had great potential for enhancing the proliferation/differentiation of osteoblasts. Moreover, the synergistic effect of Vit D-Cur loaded PCL nanofiber membrane showed a superior ability to improve the anti-inflammatory activity through M2 polarization. Furthermore, in vivo results confirmed that the defect treated with PCL/Vit D-Cur nanofiber membrane was filled with the newly formed bone after 1 month. These results indicate that the Vit D/Cur loaded membrane can be applied for potential bone regeneration therapy.